Morus alba L. Plant: Bioactive Compounds and Potential as a Functional Food Ingredient - Centhyea Chen; Umi Hartina Mohamad Razali; Fiffy Hanisdah Saikim; Azniza Mahyudin; Nor Qhairul Izzreen Mohd Noor (MDPI, 2021)
Morus alba L. (M. alba) is a highly adaptable plant that is extensively incorporated in many traditional and Ayurveda medications. Various parts of the plant, such as leaves, fruits, and seeds, possess nutritional and medicinal value. M. alba has abundant phytochemicals, including phenolic acids, flavonoids, flavonols, anthocyanins, macronutrients, vitamins, minerals, and volatile aromatic compounds, indicating its excellent pharmacological abilities. M. alba also contains high nutraceutical values for protein, carbohydrates, fiber, organic acids, vitamins, and minerals, as well as a low lipid value. However, despite its excellent biological properties and nutritional value, M. alba has not been fully considered as a potential functional food ingredient. Therefore, this review reports on the nutrients and bioactive compounds available in M. alba leaves, fruit, and seeds; its nutraceutical properties, functional properties as an ingredient in foodstuffs, and a microencapsulation technique to enhance polyphenol stability. Finally, as scaling up to a bigger production plant is needed to accommodate industrial demand, the study and limitation on an M. alba upscaling process is reviewed.